Polyphenol‐Inspired Facile Construction of Smart Assemblies for ATP‐ and pH‐Responsive Tumor MR/Optical Imaging and Photothermal Therapy. Issue 20 (6th April 2017) - Song, Xiao‐Rong; Li, Shi‐Hua; Dai, Jiayong; Song, Liang; Huang, Guoming; Lin, Ruhui; Li, Juan; Liu, Gang; Yang, Huang‐Hao
Abstract : Smart assemblies have attracted increased interest in various areas, especially in developing novel stimuli‐responsive theranostics. Herein, commercially available, natural tannic acid (TA) and iron oxide nanoparticles (Fe3 O4 NPs) are utilized as models to construct smart magnetic assemblies based on polyphenol‐inspired NPs–phenolic self‐assembly between NPs and TA. Interestingly, the magnetic assemblies can be specially disassembled by adenosine triphosphate, which shows a stronger affinity to Fe3 O4 NPs than that of TA and partly replaces the surface coordinated TA. The disassembly can further be facilitated by the acidic environment hence causing the remarkable change of the transverse relaxivity and potent "turn‐on" of fluorescence (FL) signals. Therefore, the assemblies for specific and sensitive tumor magnetic resonance and FL dual‐modal imaging and photothermal therapy after intravenous injection of the assemblies are successfully employed. This work not only provides understandings on the self‐assembly between NPs and polyphenols, but also will open new insights for facilely constructing versatile assemblies and extending their biomedical applications. Abstract : Smart magnetic assemblies featured with adenosine‐triphosphate‐responsive and pH‐facilitated disassembly capabilities are facilely constructed based on polyphenol‐inspired self‐assembly of nanoparticles. Endowed with remarkable change of the transverse relaxivity and potent "turn‐on" of fluorescence after the disassembly, the assemblies are employed for effective tumor magnetic resonance and fluorescence dual‐modal imaging and photothermal therapy.